Translation : theory and practice - Translation Workshop and Seminar (2003 : University of Dhaka); Zaman, Niaz.; PEN Bangladesh (Dhaka : Academic Press and Publishers, 2004)
Papers presented at the seminar; seminar was organized by PEN Bangladesh.
Includes bibliographical references.
Keywords: Translating and interpreting -- Bangladesh -- Congresses; Bengali language -- Bangladesh -- Translating -- Congresses; Language and languages -- Sociological aspects -- Congresses; Sociolinguistics -- Congresses; Creative thinking -- Congresses